Development of Interactive E-modules Based on Project Based Learning in Music Art Courses in High School - Pitriyanti; Susila, Heni Rita; Pebriantika, Leni (Program Magister Teknologi Pendidikan Universitas Jambi, 2026)
This study aims to develop and evaluate an interactive e-module based on Project Based Learning (PBL) for music education at the senior high school level. The research employed a Research and Development (R&D) approach using the Alessi and Trollip model, which includes planning, design, and development stages. The developed product was validated by subject matter, instructional design, and media experts, and tested through one-to-one evaluation, small group evaluation, and field testing. The results indicate that the e-module achieved high validity, with expert validation scores ranging from 85.8% to 87.6%. Product testing results also demonstrated high practicality and effectiveness, with consistent scores between 90% and 91% across all testing stages. The integration of e-module and structured PBL activities was found to enhance student engagement, support independent learning, and promote critical thinking skills. This study contributes to the development of innovative digital learning resources by integrating technology and project-based pedagogy in music education. The findings suggest that interactive e-modules can serve as effective tools for improving the quality of student-centered learning in the digital era.